LANGUAGE POLITENESS PRINCIPLES USED BY TEACHER TO BUILD STUDENTS CHARACTER IN SMK TAMANSISWA 2 KOTA PROBOLINGGO - Laili, Nur; Wafa, Hosnol; Andayani, Sri; Tjahyadi, Indra (JURNAL LITERASI, 2024)
Language phenomena often occur in schools, especially politeness. Politeness is about the principles that consider whether a speech can be said to be polite or impolite. This research analyzes the types of Bahasa Indonesia used by SMK Tamansiswa Vocational School teachers. This research implements the theory of politeness proposed by Leech which includes six maxims, namely the namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The aim of this research is to reveal which maxims Bahasa Indonesian teachers use in the daily teaching process of the six maxims. The method used is descriptive qualitative, with data collection techniques through observation, and recording. After the classification process, four maxims were found, namely the generosity maxim, approbation maxim, agreement maxim, and sympathy maxim. The total data found is 49 data. The 49 data consist of generosity maxim 33 data, approbation maxim 4 data, agreement maxim 3 data, and sympathy maxim 3 data. The research results found four maxims which include the generosity maxim, approbation maxim, agreement maxim, and sympathy maxim. Apart from that, two maxims were found that were not used by teachers, namely tact maxim, and modesty maxim. The total data found was 49 data. It can be concluded that Indonesian language teachers, especially at Tamansiswa Vocational School, have succeeded in implementing Leech politeness.